PENGGUNAAN ANTIHIPERTENSI PADA PASIEN STROKE NON HEMORAGIK DI INSTALASI FARMASI RAWAT JALAN RUMAH SAKIT X SEMARANG - Maya OCTASARI, Paulina; Veny OKTAVIANI, Anastasia (SEKOLAH TINGGI ILMU FARMASI YAYASAN PHARMASI SEMARANG, 2020)
Non-hemorrhagic stroke is a functional disorder of the brain’s neurologic deficits caused by vasocontraction due to blockage in the arterial vessel leading to the brain. There were 79% of non-hemorrhagic stroke patients are caused by hypertension. Antihypertensive therapy for the patients given as secondary therapy to prevent recurrent stroke, decreased brain edema risk, hemorrhagic risk, and prevent further vascular damage. Therefore this research aimed to evaluate antihypertensive usage in non-hemorrhagic stroke patients in the Hospital. The research is an observational descriptive with cross-sectional design and retrospective data. Data retrieval through the medical record of outpatients with ages 36-65 years were diagnosed with non-hemorrhagic stroke with or without comorbidities and National Health Insurance patients period of October - December in 2019. Data were classified based on age, gender, and antihypertensive agent, and were analyzed by calculating the percentage of patients who have decrease, stability, and increased blood pressure. 92 patients who were included in the inclusion criteria. The result showed that more male patients (68,48%), mostly age category 55-65 years (70,65%) with hypertensive (51,09%). Antihypertensive usage in non-hemorrhagic stroke is mostly used CCB group (70,65%). The percentage of patients who suffered a decrease in systolic blood pressure as much as 53 patients (57,6%), meanwhile the decrease in diastolic blood pressure as much as 63 patients (68,46%). There were 69 patients (75%) has blood pressure target therapy.